Determinant Analysis Related to Basic BCG Immunization Status in Infants - Sulistiyah Sulistiyah; Retno Dewi Prisusanti (GLOBAL HEALTH SCIENCE GROUP, 2024)
Immunization is an effort to actively create/increase a person's immunity to a certain disease. BCG immunization is given immediately after the baby is born or before the age of 1 month. BCG immunization can reduce the risk of severe tuberculosis. TB is an infectious disease caused by infection with Mycobacteriun Tuberculosis bacteria, which can spread through the droplets of people who have been infected with TB bacilli. This study aims to determine the factors associated with the status of basic BCG immunization in infants. This study is a quantitative study using a cross-sectional design.. The population in this study consists of all infants aged 2-12 months in the working area of the Kalumpang Community Health Center in Ternate City, totaling 167 infants, with a sample size of 118 respondents. The sampling technique used is simple random sampling. We collected the data using questionnaire. The statistical test used is the chi-square test, and the analysis performed includes univariate and bivariate analysis. Based on the results obtained as many as 52 (44.1%) respondents were not given BCG immunization, as many as 40 (33.9%) respondents had poor knowledge, as many as 53 (44.9%) respondents with negative attitudes as many as 76 (64.4%) respondents with working status and as many as 45 (38.1%) respondents stated that the family did not support. The results of bivariate analysis showed that there was a relationship between knowledge with a p value of 0.000, attitude with a p value of 0.000, work with a p value of 0.000 and family support with a p value of 0.001. The conclusion is that there is a relationship between factors associated with basic BCG immunization status.